Evaluating the effects of loaded sit-to-stand resistance exercises on gross motor functions in spastic diplegic children with cerebral palsy - Moslem Dehghanizadeh; Mohamad Hossein Nilforoush (Vesnu Publications, 2012)
Introduction: Muscle strength is one of the most important and effective factors in movement disorders of spastic diplegic children with cerebral palsy. Respecting the fact that strength can influence gross motor functions, the aim of this study was to measure the effects of loaded sit-to-stand resistance exercises on such functions in this group of children with cerebral palsy. Materials and Methods: 20 cerebral palsy children with spastic diplegia (12 boys and 8 girls), aged between 5 and 12 years (mean, 8.30 years), participated in this study. Loaded sit-to-stand resistance exercises were performed 3 times a week for 6 weeks. Isometric strength of hip extensor, knee extensor and ankle plantar flexor were evaluated by MMT NICHOLAS apparatus. Gross motor functions were measured via GMFM. Data were statistically analyzed through paired t test. Results: The strength of hip extensor and knee extensor increased significantly (P < 0.0001). Moreover, the scores of GMFM dimensions D and E improved significantly (P < 0.0001). Conclusion: Loaded sit-to-stand resistance exercises may enhance muscle strength of lower extremity and increase scores of GMFM. Keywords: Cerebral palsy, Exercise, Motor activity, Rehabilitation